ANALYSIS OF SKILL COMMUNICATION AND MORAL EDUCATION MENTAL RETARDATION STUDENTS - Candra Dewi; Melik Budiarti (Universitas Muhammadiyah Ponorogo, 2019)
Communication skills and moral education are key in social interaction with others. Mentally retarded students experience a disruption in developing communication and the need to provide moral education to retarded mental students. This study aims to analyze the communication skills and moral education of mental retardation students in elementary schools. This research is a descriptive study with a qualitative approach. This study used three types of data collection techniques, including observation, documentation, and interviews. The technique used to analyze data in this study is interactive data analysis consisting of the stages of data reduction, data presentation, and conclusion drawing. Based on the implementation of the study in addition to experiencing learning difficulties, mental retardation students also experience a disruption in communication. Retarded mental students have difficulty communicating with their friends and also with their teachers. The mentally retarded Shiva also has not received the maximum moral education.